2016
DOI: 10.1073/pnas.1600084113
|View full text |Cite
|
Sign up to set email alerts
|

Variants within the SP110 nuclear body protein modify risk of canine degenerative myelopathy

Abstract: Canine degenerative myelopathy (DM) is a naturally occurring neurodegenerative disease with similarities to some forms of amyotrophic lateral sclerosis (ALS). Most dogs that develop DM are homozygous for a common superoxide dismutase 1 gene (SOD1) mutation. However, not all dogs homozygous for this mutation develop disease. We performed a genome-wide association analysis in the Pembroke Welsh Corgi (PWC) breed comparing DM-affected and -unaffected dogs homozygous for the SOD1 mutation. The analysis revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 72 publications
1
37
0
1
Order By: Relevance
“…Interestingly, ≥34 repeats in ATXN2 are associated with spinocerebellar ataxia (Sproviero et al, 2017). which is an analog of ALS in humans (Ivansson et al, 2016). Whether SP110 variants are risk modifiers in humans remains to be studied in the future.…”
Section: Disease-modifier Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ≥34 repeats in ATXN2 are associated with spinocerebellar ataxia (Sproviero et al, 2017). which is an analog of ALS in humans (Ivansson et al, 2016). Whether SP110 variants are risk modifiers in humans remains to be studied in the future.…”
Section: Disease-modifier Genesmentioning
confidence: 99%
“…Such genes include the paraoxonases ( PON1 , PON2 , PON3 ), the metallothioneins, and others (Dardiotis et al., ). Finally, variants in the SP110 gene have been shown to modify the risk of degenerative myelopathy in dogs, which is an analog of ALS in humans (Ivansson et al., ). Whether SP110 variants are risk modifiers in humans remains to be studied in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The small sample size of our GWA analysis is likely to have hampered the statistical power of our study, as reflected by the magnitude of the association. However, the stringent phenotypic inclusion criteria used in this study may counterbalance the small sample size, the resulting level of association and its reliability, similarly to previous studies mapping canine complex traits [4,33]. Moreover, the small sample size of our study population may have contributed to the unexpectedly long associated locus reported here.…”
Section: Discussionmentioning
confidence: 76%
“…4,5 A protein's ability to cause disease can solely rest with expression of the mutant protein (complete penetrance) or its pathogenesis can be modified by other genetic or environmental factors. 7 This means that dog E40K mutant SOD1, and other genetic variants contribute to the DM phenotype. 7 This means that dog E40K mutant SOD1, and other genetic variants contribute to the DM phenotype.…”
Section: Introductionmentioning
confidence: 99%